THE DEVELOPMENT OF A MODEL FOR ENHANCING LEADERSHIP CAPABILITIES OF NON-ACADEMIC STAFF IN A THAI PRIVATE HIGHER EDUCATION INSTITUTION - SUWANNATARN, YUTTHANA; ASAVISANU, POONPILAS (Scholar: Human Sciences, 2022)
This exploratory sequential multiple methods design was carried out at a selected Thai private higher education institution. The research objectives of this study were 1) to determine the desired leadership capabilities of non-academic staff, 2) to determine the current leadership capabilities of non-academic staff, 3) to find the gap between the desired and current leadership capabilities of non-academic staff, 4) to assess the influence of demographic factors on the leadership capabilities of non-academic staff, and 5) to develop a model for enhancing leadership capabilities of non-academic staff. The following theories/frameworks formed this study's basis: Talent Leadership attributes, Theory of Servant Leadership, and 21st Century Skills. Self-evaluated questionnaires were distributed to 395 non-academic staff, and 25 supporting unit administrators were interviewed to identify the desired and current leadership capabilities. This study employed descriptive statistics (frequency, mean, SD), inferential statistics (t-test, one-way ANOVA, correlation analysis), and expected performance (gap analysis). The results indicated that non-academic staff practiced the overall desired leadership attributes at their workplace at a high level with an average mean score of 4.24 (SD=0.52) and the current leadership attributes with an average mean score of 3.96 (SD=0.44) according to a 5-point rating scale. There was a statistically significant difference between the desired and current leadership capabilities of non-academic staff on three primary leadership attributes at the 0.05 level (t=11.99, p<0.05). A highly significant correlation was found when utilizing Pearson's correlation coefficient to compare the desired status, the current status, and the capabilities gap of the main leadership attributes. Moreover, expected performance (gap analysis) determined a relatively high correlation level of leadership capabilities of non-academic staff with a mean score ranged from 4.17 to 4.31. The final model was developed by consolidating the findings from all the objectives and subsequent validation by 25 experts.